1990
DOI: 10.1149/1.2086948
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Mechanisms for Iron and Low Alloy Steels Exposed to the Atmosphere

Abstract: Despite extensive study over the years, the chemical processes involved in the atmospheric corrosion of iron and its alloys remain poorly understood. Most conceptual studies have ignored the chemical influence of the trace anions (CI-, NO~ , SO42-, CO2H , etc.) present in the atmosphere and in precipitation. This review, presented from the perspective of atmospheric chemistry and mineralogy, provides an analysis of rust layer formation, evolution, morphology, and composition, together with information on iron-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(80 citation statements)
references
References 84 publications
3
73
0
4
Order By: Relevance
“…It shows that the C H /C O ratio is always lower than the one of FeOOH. From these results, we can assume that the corrosion product is composed of mixed hydroxides and oxides as previously observed [3].…”
Section: Characterisation Of the Corrosion Layers Induced By Irradiationsupporting
confidence: 81%
“…It shows that the C H /C O ratio is always lower than the one of FeOOH. From these results, we can assume that the corrosion product is composed of mixed hydroxides and oxides as previously observed [3].…”
Section: Characterisation Of the Corrosion Layers Induced By Irradiationsupporting
confidence: 81%
“…The rust layers on steel exposed to outdoor atmospheric environments are porous and poorly adherent. Pore sizes with typical pore volumes constituting 5-10% of the rust volume have been found, such a structure allows the ingress of water (Graedel and Frankenthal, 1990). In the formation of these rust layers, iron released from the steel is initially oxidised to ferrous ion.…”
Section: Resultsmentioning
confidence: 95%
“…Scanning electron microscopy of the surfaces showed that the oxide had the characteristic whisker structure of the chlorine containing oxide akaganeite [I 01. This oxide has been identified in corrosion products formed on carbon steels in marine environments [5].…”
Section: Resultsmentioning
confidence: 99%
“…Under normal atmospheric conditions, it is recognized that the effectiveness of sustaining the corrosion processes decreases with time for a given amount of initially deposited salt. It is documented that chloride ions are incorporated into the iron oxide akaganeite under marine conditions [5]. Sulfate has been identified within solid corrosion products [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation